Empirical validation of the New Zealand serious non-fatal injury outcome indicator for 'all injury'. Issue 4 (27th September 2017) - Cryer, Colin; Davie, Gabrielle S; Gulliver, Pauline J; Petridou, Eleni Th; Dessypris, Nick; Lauritsen, Jens; Macpherson, Alison K; Miller, Ted R; de Graaf, Brandon
Abstract : Our purpose was to empirically validate the official New Zealand (NZ) serious non-fatal 'all injury' indicator. To that end, we aimed to investigate the assumption that cases selected by the indicator have a high probability of admission. Using NZ hospital in-patient records, we identified serious injury diagnoses, captured by the indicator, if their diagnosis-specific survival probability was ≤0.941 based on at least 100 admissions. Corresponding diagnosis-specific admission probabilities from regions in Canada, Denmark and Greece were estimated. Aggregate admission probabilities across those injury diagnoses were calculated and inference made to New Zealand. The admission probabilities were 0.82, 0.89 and 0.90 for the regions of Canada, Denmark and Greece, respectively. This work provides evidence that the threshold set for the official New Zealand serious non-fatal injury indicator for 'all injury' captures injuries with high aggregate admission probability. If so, it is valid for monitoring the incidence of serious injuries.